2009
DOI: 10.1111/j.1365-3164.2009.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of canine‐generalized demodicosis: a blind, randomized clinical trial comparing the efficacy of Advocate®(Bayer Animal Health) with ivermectin

Abstract: Advocate (moxidectin 2.5% + imidacloprid 10%) is a multiparasiticidal agent authorized for treating canine demodicosis in many countries. This blind, randomized clinical trial assessed the efficacy of Advocate at varying treatment intervals and compared it with that of oral ivermectin. Fifty dogs with generalized demodicosis were randomly assigned to one of four treatment groups: oral ivermectin (500 microg/kg once daily), Advocate applied at the authorized dose monthly (ADV1), every 2 weeks (ADV2) or weekly (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 23 publications
2
44
0
3
Order By: Relevance
“…Ivermectin at 0.44 mg/kg was prescribed orally once daily for treatment of demodicosis. Several studies show oral ivermectin at 0.3–0.6 mg/kg to be effective for treatment of demodicosis (Mueller 2004, Paterson and others 2009, Capc 2013). Ivermectin toxicosis due to ABCB1 (MDR1) gene mutation in specific breeds, including collie, Australian shepherd, English and German shepherds, herding breed crosses, longhaired whippets, Shetland sheepdogs and silken windhounds, has been identified (Yoo and other 2010, Geyer and Janko 2012, Odunayo and Kerl 2012 , Capc 2013 , Wsu 2015).…”
Section: Treatmentmentioning
confidence: 99%
“…Ivermectin at 0.44 mg/kg was prescribed orally once daily for treatment of demodicosis. Several studies show oral ivermectin at 0.3–0.6 mg/kg to be effective for treatment of demodicosis (Mueller 2004, Paterson and others 2009, Capc 2013). Ivermectin toxicosis due to ABCB1 (MDR1) gene mutation in specific breeds, including collie, Australian shepherd, English and German shepherds, herding breed crosses, longhaired whippets, Shetland sheepdogs and silken windhounds, has been identified (Yoo and other 2010, Geyer and Janko 2012, Odunayo and Kerl 2012 , Capc 2013 , Wsu 2015).…”
Section: Treatmentmentioning
confidence: 99%
“…Initial studies evaluating the spot‐on as monthly treatment for generalized demodicosis were encouraging 64 . However, clinical use did not corroborate the findings, and subsequent studies revealed that the spot‐on was more efficacious in juvenile dogs with milder forms of the disease 30 and that weekly therapy showed better results than twice monthly or monthly administration 9,65 . Based on these results, the label of this product was changed to recommend weekly administration in many countries where it has been approved for the treatment of canine demodicosis.…”
Section: Treatment Of Canine Demodicosismentioning
confidence: 99%
“…For most of the recommendations in this article, the evidence was derived from results of a recent systematic review 8 (COE I) or clinical trials (COE II). There are few randomized controlled studies published evaluating therapeutic options for canine demodicosis 9,10 . To the authors’ knowledge, there is not a single placebo‐controlled clinical trial, and the rate of spontaneous remission of dogs with generalized demodicosis is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Although both forms of canine demodicosis are usually considered as separate and distinct diseases, this may be an oversimplification because all cases of generalized demodicosis commence as localized disease. Also, there is no agreed scientific basis for a clear and consistent differentiation between localized and generalized forms, and the delineation as localized or generalized in borderline cases may be somewhat arbitrary . Demodicosis is a complex disease, and its exact pathogenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%